Poorly differentiated chordoma - Li Yang; Yixiong Liu; Yongqiang Tang; Jie Wei; Linni Fan; Yingmei Wang; Xiaohui Zhang; Hong Cheng (Human Pathology Reports, 2022)
Chordoma is a rare primary malignant bone tumor that is believed to develop from embryonic notochordal remnants. The current World Health Organization (WHO) classification system divides chordoma into three subtypes: conventional, dedifferentiated and poorly differentiated chordoma (PDC). PDC is a newly recognized subtype of chordoma with distinct clinicopathological features characterized by loss of SMARCB1 expression. It typically occurs in young adults and children, more commonly arises in the skull base and cervical spine, rarely in the sacrococcygeal region, and exhibits more aggressive clinical behavior. Histologically, PDC is composed of cohesive sheets of poorly differentiated epithelioid cells with scattered intracytoplasmic vacuoles and minimal myxoid stroma, which may evoke a broad spectrum of differential diagnoses. Molecularly, PDC bears chromosome 22q loss leading to SMARCB1/INI1 inactivation. Clinicopathological correlation, including ancillary studies to confirm the loss of SMARCB1 expression, is critical for reaching the correct diagnosis.